In vitro antitrypanosomal andantiplasmodialactivitiesofcrude extractsandessentialoilsof Ocimum gratissimum Linn fromBenin and influence ofvegetativestage - Kpadonou-Kpoviessi, Bénédicta; KPOVIESSI, Dossou Sika Salomé (My University, 2014)
Ethnopharmacological relevance: Different partsof Ocimum gratissimum Linn arelargelyusedinfolk medicine forthetreatmentofmanydiseases,someofwhichrelatedtoparasiticalinfectionsasfeversand headaches. Inordertovalidatetheiruseandtoclarifytheplantpartwhichpossessesthebest antiparasitic properties,wedecidedtoevaluatethe in vitro antiplasmodial andantitrypanosomal activities ofessentialoilsandcrudeextractsfromleaves,stemsandseedsof Ocimum gratissimum as well astheircytotoxicity. Materials andmethods: The essentialoilsandethanolcrudeextractsofleavesandstemsof Ocimum gratissimum from Benin,wereobtainedinpreandfull floweringstages.Seedsobtainedonlyinfull floweringstage,werealsoextracted.TheoilswereisolatedbyhydrodistillationandanalyzedbyGC/MS and GC/FID.Extractsandessentialoilsweretested in vitro against Trypanosomabruceibrucei and Plasmodium falciparum. Cytotoxicitywasevaluated in vitro against ChineseHamsterOvary(CHO)cells and thehumannoncancer fibroblastcellline(WI38)throughMTTassaytoevaluatetheselectivityand toxicitywasassessedagainst Artemia salina Leach. Results: The essentialoilsandnon-volatilecrudeextractsof Ocimum gratissimum weremoreactiveon Trypanosomabruceibrucei than on Plasmodium falciparum (3D7). Thisactivityvariesaccordingtothe vegetativestage(preandfull flowering)andtheplantpart(seeds,stemsandleaves)extracted.Thebest growthinhibitionof Trypanosomabruceibrucei wasobservedwithethanolcrudeextractsofleaves (IC50¼1.6670.48 μg/mL) andseeds(IC50¼1.2970.42 μg/mL) infull floweringstagewithgoodselectiv- ity (SI410).Thechemicalcompositionoftheessentialoilfromaerialparts(47compounds), characterizedbythepresenceasmainconstituentsof p-cymene, thymol, γ-terpinene, β-myrceneand α-thujene, dependsonthevegetativestage.Theoilcontainedsomeminorcompoundssuchasmyrcene (IC50¼2.2470.27 μg/mL), citronellal(IC50¼2.7671.55 μg/mL), limonene(IC50¼4.2472.27 μg/mL), with good antitrypanosomalactivities.Theseoilsandcrudeextractswerenottoxicagainst Artemia salina Leach andhadalowcytotoxicityexceptleavesandseedsethanolextractsobtainedinfull flowering which showedtoxicityagainstCHOandWI38cells. Conclusions: Our studyshowsthatethanolcrudeextractsofleavesandseedsof Ocimum gratissimum in full floweringstagecanbeagoodsourceofantitrypanosomalagents.Thisisthe first reportaboutthe relation betweentheplantpartextracted,thevegetativestageoftheplant,theantitrypanosomaland antiplasmodial activitiesandthecytotoxicityofessentialoilsandnon-volatileextractsof Ocimum gratissimum from Benin.
Keywords: Ocimum gratissimum; Essential oils; Crude extracts; Antitrypanosomal activity; Antiplasmodial activity; Cytotoxicity